PEDAGOGICAL SCIENTIFIC RESEARCH ACTIVITY IN THE HIGHER EDUCATIONAL INSTITUTION (Education in the 21st Century, 2023)
Contemporary politics when preparing professional capacity places high demands on all areas of educational activity. It emphasizes the need for active use of innovative developments and research approaches. In recent years, it has become clear that the reform of specific projects in educational institutions is the best way to look at the best practices - this is the work of each educational institution, and education functions as social stability, continuity of culture, moral, physical and mental health of young people, free, active and responsible education of a creative person. To achieve this goal, a new search and research function has appeared in educational institutions. The relevance of this article is due to the fact that today it is important to formulate professional competences, which include knowledge of the system of socio-psychological and pedagogical research on methodology and methods, the ability to organize, plan and conduct research: The discipline "Methodology and methods of pedagogical research" is of great importance in the preparation of teachers - researchers. The study of the problem was a pedagogical developments and research approaches in a higher educational institution, which was regarded as an important function in the formation of professional potential and professional competencies. The study of this problem was based on the scientific works of V. Zazvyaginsky, R. Atakhanov, V. Bordovsky,N. Borytko, A. Molozhavenko, I. Solovtsov. The search and research function is of great importance in the training of teachers and researchers. The structure of the search and research function includes a study of the approaches of the philosophical, general scientific, scientific-specific level of methodology. This contributes to the formation of the future teacher as a whole, and in the formation of the pedagogical worldview, providing the level of practical training necessary to conduct pedagogical research. The course is focused on the development of students' methodological culture, the improvement of their scientific categorical apparatus. The training program assumes that the intern will conduct research, research, analyze and summarize the results, develop and implement recommendations. The article proposes options for assignments to students discussed in seminars and practical classes. The future specialist will conduct research, analyze and summarize the results obtained, develop and implement recommendations.